2010
DOI: 10.1007/s00464-010-1125-8
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility of laparoscopic total mesorectal excision for patients with low rectal cancer after concurrent radiation and chemotherapy with bevacizumab plus FOLFOX

Abstract: Based on the controllable surgical complications and minimal invasiveness in the current patient series, laparoscopic TME is shown to be technically feasible and can be recommended for patients with advanced lower rectal cancer requiring preoperative CCRT using bevacizumab as the additional therapeutic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
0
9
2
1
Order By: Relevance
“…Several studies with additional chemotherapy have been performed using FOLFOX [16], FOLFOX plus bevacizumab [17], and capecitabine [13]. In a previous study with FOLFOX plus bevacizumab for additional chemotherapy, pCR (25.0%) was higher than the pCR (21.7%) observed in the present study, but the morbidity (21.4%) and mortality (3.6%) rates were higher in the previous study than those in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies with additional chemotherapy have been performed using FOLFOX [16], FOLFOX plus bevacizumab [17], and capecitabine [13]. In a previous study with FOLFOX plus bevacizumab for additional chemotherapy, pCR (25.0%) was higher than the pCR (21.7%) observed in the present study, but the morbidity (21.4%) and mortality (3.6%) rates were higher in the previous study than those in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Papers without rectal cancer LS and OS comparisons were excluded, which left 31 potentially eligible studies. From the overall pool of full-text articles, 18 articles were excluded for the following reasons: they did not offer available outcomes (n=4), [16][17][18][19] the study quality was low (n=3), [20][21][22] and the tumour distance from the anal verge was more than 10 cm (n=11). [23][24][25][26][27][28][29][30][31][32][33] Thirteen articles were published in English for the final metaanalysis.…”
Section: Studies Selectedmentioning
confidence: 99%
“…Those changes may cause mucosal atrophy, intestinal wall fibrosis and vascular sclerosis; may make stapler application more difficult; and may increase the rate of persistent leakage. To the contrary, several studies reported that preoperative radiation did not affect technical feasibility nor significantly increase surgical morbidities or complications [29,30]. In this study, there is no association between neoadjuvant chemoradiation and intra-operative double-stapled anastomotic complications.…”
Section: Discussionmentioning
confidence: 54%